Plasma and red blood cell proteome in sickle-cell disease - Charro, Nuno (2012)
Sickle-cell disease (SCD) is a clinically heterogeneous autosomal recessive monogenic chronic anaemia characterized by recurrent episodes of severe vaso-occlusion, haemolysis and infection. Painful crises are the major SCD clinical manifestation probably due to significant increase in dense red blood cells (RBC) and reduction of their ability to pass through capillaries. Using proteomic strategies, we aim to discover novel and better SCD prognosis biomarkers as early predictors of the transition from steady-state to crisis namely vaso-occlusive episodes, thus, allowing a prompt and specific therapeutic intervention